Aspectos do processo de recolhimento do fundo documental da antiga Escola de Química Industrial do Pará ao Arquivo Central da Universidade Federal do Pará - SILVA, Marciel Cardoso (2023)
The research aims to describe aspects of the collection process of the documentary fund of the former School of Industrial Chemistry of Pará to the Central Archive (AC) of the Federal University of Pará (UFPA). It is intended, with this, to demonstrate the importance of preserving this fund for the memory of the institution. The methodological procedure was carried out through bibliographic and documentary research and a technical visit to the custodian body, where a semi-structured interview was carried out with one of the servants responsible for organizing the fund. As a result, it demonstrates the importance of preserving the documentary funds of the old schools for the institutional memory of UFPA and points out possibilities for historical research in the documentary fund addressed, indicating perspectives for the use of this fund.